Incorporating lesson study in assessing impact of algebraic mastery learning module on secondary school students' mathematics performance and anxiety - Davrajoo, Elenchothy (2013)
The purpose of this study was to investigate the impact of using Algebraic Mastery Learning Module with incorporation of Lesson Study on Form Four students’ performance and mathematics anxiety toward mathematics learning in a national secondary school. The study utilized the true experimental design using the randomized pre-post test control group design consisting of an experimental group (n = 28) using the Algebraic Mastery Learning Module (AMaLM) teaching and a control group (n = 27) using the Algebraic Conventional Learning Module (ACoLM) teaching for four weeks of teaching and learning duration. Both groups were compared on cognitive variables (overall mathematics performance, algebraic conceptual knowledge-ACK, algebraic procedural knowledge-APK, and algebraic utility knowledge-AUK) and affective variables, (overall mathematics anxiety, mathematics class climate anxiety, mathematics inability anxiety, mathematics abstraction anxiety, mathematics test anxiety, mathematics beliefs and anxiety symptoms). Additional measures such as number of errors, type of errors made by subjects during solving test problems, students’ views on AMaLM and teachers’ views on using AMaLM through Lesson Study were studied. Two instruments were used in this study, namely Algebraic Comprehension Test (ACT),Students Revised Math Anxiety Rating Scale (S-RMARS) with the use of AMaLM and ACoLM. The results of ANCOVA indicated that students from AMaLM (treatment) group performed better significantly on their overall algebraic performance (ACK, APK and AUK) (72.54; SD=8.66). Hence, there was significant impact of the different instructional approach, favouring the AMaLM for the learning of mathematics among students. Consistently the results of ANCOVA for overall mathematics anxiety (mathematics class climate anxiety, mathematics inability anxiety, mathematics abstraction anxiety, mathematics test anxiety, symptoms of mathematics anxiety) (2.39;SD= 0.47) also showed that there were significant mean differences between the two groups, with the participants from AMaLM group showing lower mathematics anxiety compared to the ACoLM group. ANCOVA test on the means performance of retention test also showed that participants from AMaLM group significantly performed better than the participants from ACoLM group. Further students in experimental group showed overall favourable views towards the AMaLM usage. The teachers involved expressed supportive views toward the Lesson Study technique and the content of AMaLM in developing the fundamental algebra for students. These results seem to support the contention that the use of mastery learning based instruction AMaLM with incorporation of Lesson Study reduce mathematics anxiety hence increase performance of mathematics. Overall, the results of the study suggested that there was sufficient evidence to conclude that the use of AMaLM in learning and incorporation of Lesson Study in teaching mathematics can improve students’ confidence toward working on algebraic based problem solving and improve the performance.